Modificações comportamentais em aranhas orbitelas (Araneae: Tetragnathidae, Nephilidae, Araneidae) atacadas por vespas parasitóides (Ichneumonidae, Pimplinae, Polysphinctini) - Sobczak, Jober Fernando (2009)
Parasitoid wasps use a wide diversity of arthropods as food for their larvae. Among the koinobiont species, (those whose development of the parasitoid does not interrupt the normal activities of the host), there is a group of wasps that it uses exclusively spiders as host. In the group, Polysphincta (Hymenoptera, Ichneumonidae, Pimplinae), some species are able to alter the behaviour of their hosts just before of pupation. These behavioral modifications, that may promote an increasing in the survival probability of the parasitoids, are rare in this type of interaction. In this work, which was divided in three chapters, new cases of behavioral manipulation of hosts are described and one of them, the interaction between the spider Nephila clavipes (Nephilidae) and the wasp Hymenoepimecis bicolor (Ichneumonidae) is analyzed in details. In the first chapter we described two new species of wasps of the genus Hymenoepimecis that attack spiders building of orbicular webs. The first species described, Hymenoepimecis n. sp. 1., parasite females of Leucauge roseosignata, inducing a behavior in the spider that resulted in the construction of a modified web. The modified web of this host is composed of only three reinforced threads. The cocoon remains fixed in in the center of this web by a suspended thread. In the second described species, Hymenoepimecis n. sp. 2., parasitoid of females of Manogea porracea, we did not observe a modification in the normal web architecture. Nevertheless, we observed that the cocoon of the parasitoid occupies a distinct position in the web. In this case, it is possible that the parasitoid could induce the replacement of the host for another highly protected site within the web In the second chapter, we analyzed the interaction between Hymenoepimecis bicolor and Nephila clavipes, and observed that there is a modification in the architecture of the web at a specific moment of larval development. The larva induces the spider to build a modified xiii web in the last three days that precede its death. This modification of the web construction behavior and consequently the change in his architecture, possibly is promoted by the inoculation of some substance in the host. The modified web is composed of only a few radii and spires, surrounded by a complex structure of barrier threads. The barrier probably confers additional protection for the cocoon. In this chapter we also tested whether the modifications in the web could be the result of poor nutritional condition, promoted by the continuous exploration of the host by the parasitoid larva. We conducted an experiment of food deprivation that showed that, even after 21 days without food, unparasitized spiders keep building webs with a normal number of radii and spirals. In the third chapter we described the male of Hymenoepimecis bicolor and investigated the influence of web aggregations and host body size in the susceptibility of females of N. clavipes to H. bicolor. We did not observe an influence of the number of spiders in the aggregations in the probability of parasitism. The body size of the spider, on the other hand, was a very important factor in the determination of the risks of parasitism. Spiders with small body size were more susceptible to attacks than large spiders. In this chapter we also describes the attacking behavior of the parasitoid from host the immobilization to oviposition. The oviposition behavior begins with a short recognition flight around the web. After checking the spider position, the parasitoid darted a straight attack to the centre of the web, reaching the host straightly and paralyzing the spider with the introduction of the ovipositor in its mouth. After immobilizing the host the parasitoid inspects the abdomen, possibly searching for another larva or egg before begin the oviposition. The spider recovers the movements soon after the oviposition and continues its normal activities, capturing prey and constructing normal webs, until three days before the larva reach the third instar.